Pozorna lekkość bytu - estetyzacja w fotografii dokumentalnej - ZARYCHTA, ANNA M. (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
The starting point for analyzing aestheticization processes in contemporary documentary photography in this text are both the “poetic” images of lightness in literature and culture analyzed in a lecture by Italo Calvino (Six Memos for the Next Millennium) and the critical thought of Wolfgang Welsch on intentional aestheticization processes in the real world. According to Welsch, these processes, through specific procedures of “lavishing lightness”, cease to be a binding image of the world and become part of a culture game (Grenzgange der Asthetik). Examples selected for analysis include award-winning documentary photography, including war photography, represented by the work of Georges Merillon, Sebastiao Salgado, Luc Delahaye, Simon Norfolk and Tim Hetherington. These ‘aestheticization procedures’ are outlined in this text in the context of the history of photography perceived as its “struggle” for a place in the history of art, as well as in the context of the theoretical considerations which accompany these processes.